(untitled) (Research, Society and Development, 2020)
Objective: To analyze the relationship between personality traits and self-care in family caregivers of elderly people with Alzheimer’s. Methods: Cross-sectional study, with 118 family caregivers of elderly people with Alzheimer’s, participating in two centers for Elderly Health Care in the period from May to December 2015. Results: 38.1% of caregivers had low neuroticism; 46.6% had average extraversion; 45.8% had an average opening; 36.4% showed high kindness and 40.7% of caregivers showed high conscientiousness. Measurement of the Appraisal of Self Care Agency Scale-Revised - ASA-R - factor “Tendo Poder” - average of 4.07 / standard deviation 0.81; “Developing Power” - average of 4.17 / standard deviation of 0.63 and “Missing Power” - average of 2.81 / standard deviation 1.11, showing greater variation. There was a significant and negative influence of Neuroticism on the “Lacking Power” factor. Conclusion: It is necessary to know the profile, the personality traits and the specific valuation of the self-care scale in its dimensions to direct assistance.